Особливості організації віддалених комунікацій при розробці програмного забезпечення - Длугунович, Наталя (Видавництво Львівської політехніки, 2016)
The article describes some aspects of remote communication for team projects developing software, which are territorially separated. The article has given recommendations about organizing of remote communication for efficient team work.
Keywords: територіально розподілена команда; віддалені комунікації; канали комунікації; інструменти комунікацій